Power and Informality in Urban Africa Ethnographic Perspectives - Stark, Laura; Teppo, Annika Björnsdotter (Africa Now, 2022)
Urban Africa is undergoing a transformation unlike anywhere else in the world, as unprecedented numbers of people migrate to rapidly expanding cities. But despite the growing body of work on urban Africa, the lives of these new city dwellers have received relatively little attention, particularly when it comes to crucial issues of power and inequality. This interdisciplinary collection brings together contributions from urban studies, geography, and anthropology to provide new insights into the social and political dynamics of African cities, as well as uncovering the causes and consequences of urban inequality. Featuring rich new ethnographic research data and case studies drawn from across the continent, the collection shows that Africa's new urbanites have adapted to their environs in ways which often defy the assumptions of urban planners. By examining the experiences of these urban residents in confronting issues of power and agency, the contributors consider how such insights can inform more effective approaches to research, city planning and development both in Africa and beyond.